2020
DOI: 10.1590/s1984-29612019107
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Toxoplasma gondii, Neospora caninum and Sarcocystis neurona antibodies in wild red-tailed Amazon parrots (Amazona brasiliensis)

Abstract: Toxoplasma gondii, Neospora caninum and Sarcocystis neurona are obligate intracellular parasites within the phylum Apicomplexa. The red-tailed Amazon parrot (Amazona brasiliensis) is a near-threatened species of psittacine that is endemic to the Atlantic Forest of Brazil and has been designated as a bioindicator because of its sensitivity to environmental qualitative status and changes. The aim of this study was to evaluate the presence of antibodies against T. gondii, N. caninum and S. neurona in wild red-tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A total of 102 samples from birds were genotyped in this summary (Table 10), including 75 from viable T. gondii isolates (Table 2) and 27 from DNA extracted from tissues of birds (Table 10). Overall, genotype distribution follows the global patterns recognized previously (Shwab et al, 2014;Su and Dubey, 2020), with ToxoDB genotypes #1 and #3 (collectively known as Type II), and genotype #2 (known as Type III) being dominant in Africa and Europe. Most genotypes identified in the Americas were diverse and different from those in the Old World.…”
Section: Clinical Toxoplasmosis In Wild Birdsmentioning
confidence: 56%
See 1 more Smart Citation
“…A total of 102 samples from birds were genotyped in this summary (Table 10), including 75 from viable T. gondii isolates (Table 2) and 27 from DNA extracted from tissues of birds (Table 10). Overall, genotype distribution follows the global patterns recognized previously (Shwab et al, 2014;Su and Dubey, 2020), with ToxoDB genotypes #1 and #3 (collectively known as Type II), and genotype #2 (known as Type III) being dominant in Africa and Europe. Most genotypes identified in the Americas were diverse and different from those in the Old World.…”
Section: Clinical Toxoplasmosis In Wild Birdsmentioning
confidence: 56%
“…Most genotypes identified in the Americas were diverse and different from those in the Old World. Of interest is the predominance of ToxoDB genotype #9 (Chinese 1) in China and its rare occurrence in Mexico (Alvarado-Esquivel et al, 2011;Shwab et al, 2014). Type I isolates (ToxoDB genotype #10) are considered rare worldwide.…”
Section: Clinical Toxoplasmosis In Wild Birdsmentioning
confidence: 99%
“…Besides, Andrade et al (2016) serologically examined 67 different psittacine species and found anti-T. gondii antibodies in 1.3% of the examined birds. However, the recent investigation of Sato et al (2020) revealed the absence of antibodies against T. gondii in wild red-tailed Amazon parrots. For the first time in China, the anti-T. gondii antibodies were found in 13.63% of Cockatiels and 3.85% of Lovebirds (Zhang et al, 2014).…”
Section: Toxoplasmosis In Pet Birdsmentioning
confidence: 99%
“…Large quantities of parasites are required as antigens for agglutination tests: in the case of S. neurona, multiplication of merozoites in cell cultures is poor in comparison with related parasites (Ellison et al, 2001), which may hamper preparation of antigen for SAT. Most seroepidemiological surveys for S. neurona in wildlife have been carried out using IFAT with specific or cross-reactive secondary antibodies (Jankowski et al, 2015;Onuma et al, 2014;Sato et al, 2020).…”
Section: /22mentioning
confidence: 99%
“…Limited investigations have been conducted on S. neurona in South American birds. In the state of Paraná, southern Brazil, 51 red-tailed Amazon parrots (Amazona brasiliensis) were tested for the parasite using IFAT and none of them were seropositive for S. neurona (Sato et al, 2020). So far, there have not been any confirmed cases of infection by S. neurona in South American birds.…”
Section: /22mentioning
confidence: 99%